Capacitor, circuit, circuit board and device
By using anti-perovskite-type compounds in capacitors and cations and anions, the relative dielectric constant of the dielectric is improved, the problem of limited electrostatic capacity of the perovskite-type structure is solved, and high electrostatic capacity and high frequency response are achieved capacitor.
Patent Information
- Application Number
- CN202380043966.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-05-31
- Filing Date
- 2023-05-02
- Publication Date
- 2025-01-10
AI Technical Summary
The relative dielectric constant of the existing perovskite-type compounds is difficult to increase at room temperature, resulting in limited electrostatic capacity of the capacitor, and the anti-perovskite-type structure is slow to respond in high-frequency applications, making it difficult to exert high output.
Using compounds containing antiperovskite-type structures as dielectrics, the capacitance of the capacitor is increased by placing cations on multiple octahedrals that share the vertex and anions in the center of the octahedral to increase the relative dielectric constant. .
The high relative dielectric constant of the dielectric is achieved, and the capacitance of the capacitor is significantly improved. It is suitable for high-frequency applications and meets the needs of miniaturization and high-performance electronic equipment.
Smart Images

Figure CN119301715A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to capacitors, circuits, circuit boards, and devices. Background Art
[0002] Conventionally, attempts have been made to use compounds having a perovskite structure in devices such as solar cells.
[0003] For example, Patent Document 1 describes a ferroelectric memory element in which a ferroelectric layer is sandwiched between a pair of electrodes. The ferroelectric layer contains a predetermined halide-based organic-inorganic hybrid perovskite compound or an inorganic perovskite compound. As halide-based organic-inorganic hybrid perovskite compounds, for example, CH3NH3PbI3, C2H5NH3PbI4, CH3NH3SnI3, and C2H5NH3SnI4 are shown. As inorganic perovskite compounds, CsSnI3 and the like are shown.
[0004] Patent Document 2 describes that an antiperovskite-based solid electrolyte is used as a solid electrolyte for a predetermined capacitor.
[0005] A ferroelectric material with an antiperovskite structure represented by [(CH3)2(F-CH2CH2)NH]3(CdCl3)(CdCl4) is described in Non-Patent Document 1. In the antiperovskite structure, it can be understood that anions are arranged at the centers of multiple octahedrons sharing a face, and cations are arranged at the vertices of the multiple octahedrons.
[0006] Prior Art Literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2016-171152
[0009] Patent Document 2: Japanese Patent Application Publication No. 2019-21795
[0010] Non-patent literature
[0011] Non-patent literature 1: Zhong-Xia Wang, Yi Zhang, Yuan-Yuan Tang, Peng-Fei Li, andRen-Gen Xiong, “Fluoridation Achieved Antiperovskite Molecular Ferroelectricin[(CH3)2(F-CH2CH2)NH]3(CdCl3)(CdCl4)” J.Am.Chem.Soc.2019,141,10,4372-4378. Summary of the invention
[0012] The present disclosure provides a capacitor that includes a dielectric containing an antiperovskite-type compound and is advantageous from the viewpoint of high electrostatic capacitance.
[0013] The capacitor disclosed herein comprises:
[0014] a first electrode;
[0015] a second electrode; and
[0016] a dielectric disposed between the first electrode and the second electrode,
[0017] The dielectric contains an antiperovskite-type compound,
[0018] The antiperovskite structure has a portion where cations are arranged at the vertices of a plurality of octahedrons that share a vertex, and anions are arranged at the center of the octahedron.
[0019] According to the present disclosure, it is possible to provide a capacitor that includes a dielectric containing a compound having an antiperovskite structure and is advantageous in terms of high electrostatic capacitance. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a diagram showing the crystal structure of CaTiO3.
[0021] Figure 2 It is a diagram showing the crystal structure of BaNiO3.
[0022] Figure 3 This is a diagram showing an example of a capacitor of the present disclosure.
[0023] Figure 4 It is a diagram showing the crystal structure of CsSnCl3.
[0024] Figure 5A It is a diagram showing the crystal structure of CsSn2Cl5.
[0025] Figure 5B is a diagram showing the crystal structure of CsSn2Cl5 represented by a coordination polyhedron centered on an anion.
[0026] Figure 5C It is viewed along the negative direction of the c-axis Figure 5B Figure 2 shows the crystal structure of the
[0027] Fig. 6A is a diagram showing the crystal structure of CsSn2Cl4Br represented by a coordination polyhedron centered on an anion.
[0028] Figure 6B It is viewed along the negative direction of the c-axis Fig. 6A Figure 2 shows the crystal structure of the
[0029] Fig. 7A : is a diagram showing the crystal structure of CsSnPbCl5 represented by a coordination polyhedron centered on an anion.
[0030] Figure 7B It is viewed along the negative direction of the c-axis Fig. 7A Figure 2 shows the crystal structure of the
[0031] Fig. 8A KCsSn4Cl is represented by a coordination polyhedron centered on the anion. 10 Diagram of the crystal structure.
[0032] Figure 8B It is viewed along the negative direction of the c-axis Fig. 8A Figure 2 shows the crystal structure of the
[0033] Fig. 9A is a diagram showing the crystal structure of Cs3CoCl5 represented by a coordination polyhedron centered on an anion.
[0034] Fig. 9B It is viewed along the negative direction of the c-axis Fig. 9A Figure 2 shows the crystal structure of the
[0035] Fig. 10A : is a diagram showing the crystal structure of Ba3AlO4F represented by coordination polyhedra centered on anions.
[0036] Fig. 10B It is viewed along the negative direction of the c-axis Fig. 10A Figure 2 shows the crystal structure of the
[0037] Fig.11A It is a diagram showing the crystal structure of BaLa2ZnO5 represented by a coordination polyhedron centered on an anion.
[0038] Fig. 11B It is viewed along the negative direction of the c-axis Fig.11A Figure 2 shows the crystal structure of the
[0039] Fig. 12A is a diagram showing the crystal structure of CsBa2SnS4Cl represented by a coordination polyhedron centered on an anion.
[0040] Fig. 12B It is viewed along the negative direction of the c-axis Fig. 12A Figure 2 shows the crystal structure of the
[0041] Fig.13A is a diagram showing the crystal structure of La2CuSbS5 represented by a coordination polyhedron centered on an anion.
[0042] Fig. 13BIt is viewed along the negative direction of the c-axis Fig.13A Figure 2 shows the crystal structure of the
[0043] Fig.14A is a diagram showing La4FeSb2S represented by a coordination polyhedron centered on an anion 10 Diagram of the crystal structure.
[0044] Fig. 14B It is viewed along the negative direction of the c-axis Fig.14A Figure 2 shows the crystal structure of the
[0045] Fig.15A is a diagram showing the crystal structure of Ba4In2Te2S5 represented by coordination polyhedra centered on anions.
[0046] Fig. 15B It is viewed along the negative direction of the c-axis Fig.15A Figure 2 shows the crystal structure of the
[0047] Fig.16A is a diagram showing the crystal structure of Y2HfS5 represented by a coordination polyhedron centered on an anion.
[0048] Fig. 16B It is viewed along the negative direction of the c-axis Fig.16A Figure 2 shows the crystal structure of the
[0049] Fig.17A is a diagram showing the crystal structure of TlPb2Cl5 represented by a coordination polyhedron centered on an anion.
[0050] Fig. 17B It is viewed along the negative direction of the c-axis Fig.17A Figure 2 shows the crystal structure of the
[0051] Fig.18A 2 is a cross-sectional view showing still another example of the capacitor of the present disclosure.
[0052] Fig.18B 2 is a cross-sectional view showing still another example of the capacitor of the present disclosure.
[0053] Fig. 18C 2 is a cross-sectional view showing still another example of the capacitor of the present disclosure.
[0054] Fig.19A It is a diagram schematically showing an example of a circuit of the present disclosure.
[0055] Fig.19B This is a diagram schematically showing an example of a circuit board of the present disclosure.
[0056] Fig.19C This is a diagram schematically showing an example of the device disclosed in the present invention.
[0057] Fig. 20 It is a diagram schematically showing a method for evaluating the relative dielectric constant of the dielectrics of each Example and each Comparative Example.
[0058] Fig.21 This is a graph showing the X-ray diffraction (XRD) pattern of the dielectric material of Example 1.
[0059] Fig. 22 This is a graph showing the XRD spectrum of the dielectric material of Comparative Example 2. DETAILED DESCRIPTION
[0060] (Insights that form the basis of this disclosure)
[0061] In recent years, with the miniaturization and high functionality of electronic equipment, the miniaturization, high integration and high frequency of electronic circuits have been continuously promoted. Regarding electronic components used in electronic circuits, miniaturization and high performance are also required. For example, it is believed that if a small capacitor with high electrostatic capacitance can be provided, it can contribute to the miniaturization and high performance of electronic components. Electrostatic capacitance depends on the relative dielectric constant of the dielectric used for the capacitor. The higher the relative dielectric constant, the greater the electrostatic capacitance.
[0062] As a perovskite type structure having a composition of ABX3, there may be a CaTiO3 type crystal structure and a BaNiO3 type crystal structure. Figure 1 and Figure 2 Figures 1 and 2 are diagrams showing the crystal structure of CaTiO3 and the crystal structure of BaNiO3, respectively. Figure 1 As shown in the crystal structure of CaTiO3, Ca is configured at the A site. 2+ , Ti is configured at the B site 4+ , O is configured at the X site 2- In the crystal structure of CaTiO3, one Ti 4+ There are 6 O atoms around 2- , Ti is configured at the center of multiple octahedrons sharing vertices 4 + The vertices of these octahedrons are configured with O 2- .like Figure 2 As shown in the crystal structure of BaNiO3, Ba is configured at the A site. 2+ , Ni is configured at the B site 4+ , O is configured at the X site 2- In the crystal structure of BaNiO3, one Ni 4+ There are 6 O atoms around 2- , Ni is configured at the center of multiple octahedrons sharing the same face 4+ The vertices of these octahedrons are configured with O2- .
[0063] The relative dielectric constant of a compound having a perovskite structure at room temperature is difficult to become high, and it is difficult to further improve the electrostatic capacitance of a capacitor having a dielectric containing such a compound. In the capacitor described in Patent Document 2, a compound of an antiperovskite structure is used as a solid electrolyte, and it is not envisioned to use a compound of an antiperovskite structure as a dielectric of a capacitor. Furthermore, in the capacitor described in Patent Document 2, charge is stored by ion conduction whose response speed is slower than polarization, so it can be understood that it is difficult for the capacitor to exert a high output. In the antiperovskite structure of the ferroelectric material described in Non-Patent Document 1, it can be understood that anions are arranged at the center of multiple octahedrons sharing a face, and cations are arranged at the vertices of the multiple octahedrons. The relative dielectric constant of the ferroelectric material described in Non-Patent Document 1 at room temperature is difficult to be said to be high. In Non-Patent Document 1, it is not envisioned to apply the ferroelectric material to a capacitor. If the relative dielectric constant of the ferroelectric material at room temperature is considered, it is difficult to say that the ferroelectric material is suitable for a capacitor.
[0064] In view of such a situation, the inventors have repeatedly conducted in-depth research on whether it is possible to increase the electrostatic capacitance of a capacitor while having a dielectric containing a compound of an antiperovskite structure. As a result, the inventors have newly discovered that a dielectric containing a specific antiperovskite structure compound can have a high relative dielectric constant. Based on this new insight, the inventors have developed the capacitor disclosed in the present invention.
[0065] (Overview of one aspect of the present disclosure)
[0066] A capacitor according to a first aspect of the present disclosure includes:
[0067] a first electrode;
[0068] a second electrode; and
[0069] a dielectric disposed between the first electrode and the second electrode,
[0070] The dielectric contains an antiperovskite-type compound,
[0071] The antiperovskite structure has a portion where cations are arranged at the vertices of a plurality of octahedrons that share a vertex, and anions are arranged at the center of the octahedron.
[0072] According to the first aspect, the dielectric is likely to have a high relative dielectric constant, and the capacitor is likely to have a high electrostatic capacitance.
[0073] In the second aspect of the present disclosure, for example, in the capacitor according to the first aspect, the compound may contain ions of an element in at least one group selected from Group 13, Group 14, and Group 15. According to the second aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0074] In the third embodiment of the present disclosure, for example, in the capacitor involved in the second embodiment, the ions may also have lone electron pairs. According to the third embodiment, the electrons constituting the lone electron pairs are difficult to combine with the surrounding ions. Therefore, the electronic state in the above-mentioned ions is prone to become unstable, and the dielectric is prone to have a desired crystal structure. As a result, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0075] In a fourth aspect of the present disclosure, for example, in the capacitor according to any one of the first to third aspects, the compound may include a member selected from the group consisting of In + , Tl + ,Ge 2+ Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ According to the fourth aspect, the dielectric is more likely to have a high relative permittivity, and the capacitor is more likely to have a high electrostatic capacitance.
[0076] In the fifth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a composition represented by DE2Q5, in which D and E are cations and Q is an anion. According to the fifth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0077] In the sixth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a composition represented by DE2Q4R, in which D and E are cations, and Q and R are anions. According to the sixth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0078] In the seventh aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a composition represented by DEGQ5, in which D, E, and G are cations and Q is an anion. According to the seventh aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0079] In the eighth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a composition represented by DEGQ4R, in which D, E, and G are cations, and Q and R are anions. According to the eighth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0080] In a ninth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have DEG4Q 10 The composition represented by , in which D, E and G are cations, and Q is an anion. According to the ninth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0081] In the 10th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by DEG4Q8R2, in which D, E and G are cations and Q is an anion. According to the 10th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0082] In the 11th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by D3EQ5, in which D and E are cations and Q is an anion. According to the 11th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0083] In the twelfth aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a composition represented by D3EQ4R, in which D and E are cations, and Q and R are anions. According to the twelfth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0084] In the 13th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by DE2GQ5, in which D, E and G are cations and Q is an anion. According to the 13th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0085] In a 14th aspect of the present disclosure, for example, in the capacitor according to any one of the first to fourth aspects, the compound may have a D6EQ 10The composition represented by , in which D and E are cations, and Q is an anion. According to the fourteenth aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0086] In the 15th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by D6EQ8R2, in which D and E are cations, and Q and R are anions. According to the 15th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0087] In the 16th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by D2E4GQ5, in which D, E and G are cations and Q is an anion. According to the 16th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0088] In the 17th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by DE2GQ4R, in which D, E and G are cations, and Q and R are anions. According to the 17th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0089] In the 18th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by D2E4GQ8R2, in which D, E and G are cations, and Q and R are anions. According to the 18th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0090] In the 19th aspect of the present disclosure, for example, in the capacitor involved in any one of the 1st to 4th aspects, the compound may have a composition represented by D2E4Q7, in which D and E are cations and Q is an anion. According to the 7th aspect, the dielectric is more likely to have a high relative dielectric constant, and the capacitor is more likely to have a high electrostatic capacitance.
[0091] A circuit according to a 20th aspect of the present disclosure includes the capacitor according to any one of the first aspect to the 19th aspect. According to the 20th aspect, the capacitor easily has a high electrostatic capacitance, and the circuit easily exhibits desired performance.
[0092] A circuit board according to a 21st aspect of the present disclosure includes the capacitor according to any one of the 1st to 19th aspects. According to the 21st aspect, the capacitor easily has a high electrostatic capacitance, and the circuit board easily exhibits desired performance.
[0093] A device according to a 22nd aspect of the present disclosure includes the capacitor according to any one of the 1st to 19th aspects. According to the 22nd aspect, the capacitor easily has a high electrostatic capacitance, and the device easily exhibits desired performance.
[0094] (Implementation Method)
[0095] Hereinafter, embodiments of the present disclosure will be described with reference to the drawings. The present disclosure is not limited to the following embodiments.
[0096] Figure 3 is a cross-sectional view showing an example of a capacitor disclosed in the present invention. Figure 1 As shown, the capacitor 1a includes a first electrode 11, a second electrode 12, and a dielectric 20. The dielectric 20 is arranged between the first electrode 11 and the second electrode 12. The dielectric 20 includes a compound of an antiperovskite structure. The antiperovskite structure of the compound has a portion in which cations are arranged at the vertices of a plurality of octahedrons sharing a vertex and anions are arranged at the centers of these octahedrons. The compound includes, for example, an ionic crystal.
[0097] Figure 4 : is a diagram showing the crystal structure of CsSnCl 3. CsSnCl 3 has a perovskite structure. Figure 5A is a diagram showing the crystal structure of CsSn2Cl5. Figure 5B is a diagram showing the crystal structure of CsSn2Cl5 represented by a coordination polyhedron centered on an anion. Figure 5C It is viewed along the negative direction of the c-axis Figure 5B The crystal structure shown in the figure. CsSn2Cl5 has an antiperovskite structure. The antiperovskite structure is a structure in which the configuration of cations and anions in the ABX3 of a conventional perovskite compound is reversed. In other words, the positive and negative charges of the ions occupying a specific site in the perovskite compound are opposite to the positive and negative charges of the ions occupying the specific site in the antiperovskite compound. Figure 4 As shown, in CsSnCl3, Cs + , with Sn at the B site 2+ , Cl is configured at the X site - On the other hand, Figure 5B As shown, in CsSn2Cl5, Cl4 is configured at the A site 4- , with Cl at site B - , Cs is configured at the X site+ or Sn 2+ In other words, CsSn2Cl5 is represented as (Cl4)Cl(CsSn2) in ABX3 notation. Figure 5B As shown, CsSn2Cl5 has cations Cs arranged at the vertices of multiple octahedrons sharing a vertex. + or Sn 2+ , and the anion Cl is arranged at the center of the octahedron - . According to first-principles calculations, the relative dielectric constant of CsSnCl3 is calculated to be 39.4, and the relative dielectric constant of CsSn2Cl5 is calculated to be 79.5. Therefore, a compound of an antiperovskite structure having a portion in which cations are arranged at the vertices of multiple octahedrons sharing vertices and anions are arranged at the center of the octahedron can be expected to have a relative dielectric constant higher than that of a perovskite compound. In addition, as mentioned above, in the ferroelectric material of the antiperovskite structure described in non-patent document 1, it can be understood that anions are arranged at the center of multiple octahedrons sharing a face, and cations are arranged at the vertices of the multiple octahedrons. According to non-patent document 1, it is difficult to say that the relative dielectric constant of the ferroelectric material at room temperature is high. Therefore, from the viewpoint of a high relative dielectric constant, it is considered important that a compound of an antiperovskite structure has a portion in which cations are arranged at the vertices of multiple octahedrons sharing vertices and anions are arranged at the center of the octahedron. According to the research of the present inventors, it is believed that the presence of such a site in the antiperovskite structure makes it easier for ions to be arranged in a straight line in the antiperovskite structure, and polarization is easier to increase. Therefore, the dielectric 20 is easier to have a high relative dielectric constant, and the electrostatic capacitance of the capacitor 1a is easier to increase.
[0098] The cations in the antiperovskite structure compound contained in the dielectric 20 are not limited to specific ions. For example, the compound contains ions of an element in at least one group selected from Group 13, Group 14, and Group 15. In this case, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance.
[0099] In the antiperovskite structure compound contained in the dielectric 20, the ion of an element in at least one group selected from the 13th group, the 14th group, and the 15th group has, for example, a lone electron pair. A lone electron pair is an electron pair formed by two electrons belonging to a specific atom and is not shared with other atoms. For example, the ion Sn of Sn, which is an element in the 14th group, is 2+ Has a lone pair of electrons. Sn 2+The two electrons that fill the outermost s orbital form a lone electron pair. The electrons that form the lone electron pair are difficult to combine with the surrounding ions, which can cause an unstable electronic state or a special crystal structure. Therefore, if the cation in the dielectric 20 has a lone electron pair, the relative dielectric constant of the dielectric 20 tends to be high. On the other hand, as Sn ions, in addition to Sn 2+ Sn 4+ . Sn 4+ It is formed by taking away 4 electrons from Sn, and the outermost s orbital becomes empty. 4+ There is no lone electron pair. In this case, a crystal structure with a low coordination number is easily formed, and the relative dielectric constant of the material is difficult to increase.
[0100] For example, all or part of the ions of an element of at least one group selected from Group 13, Group 14, and Group 15 contained in the antiperovskite structure compound may have lone electron pairs.
[0101] The cations in the antiperovskite-type compound contained in the dielectric 20 include, for example, In + , Tl + ,Ge 2+ Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ In this case, the dielectric 20 is more likely to have a high relative permittivity, and the capacitor 1a is more likely to have a high electrostatic capacitance.
[0102] The cations in the antiperovskite-type compound contained in the dielectric 20 may include Li + 、Na + , K + , Rb + and Cs + Alkali metal ions such as Ba 2+ Alkaline earth metal ions.
[0103] The anions in the antiperovskite structure compound contained in the dielectric 20 are not limited to specific anions. The anions may be halogen ions, O 2- , which can be S 2- , can be Cl4 4- 、(CoCl4) 2- 、(AlO4) 5- 、(ZnO4) 6- 、(SnS4) 4- and (InSTe2)2 6- Polyatomic ions.
[0104] In order to determine which of the specific elements in the antiperovskite-type compound is a cation or anion, for example, X-ray photoelectron spectroscopy (XPS) can be used for determination. In the case where the binding energy obtained by XPS determination is lower than the binding energy in the elemental metal, it can be determined that the element as the object of determination is negatively charged and the element exists as an anion. On the other hand, in the case where the binding energy obtained by XPS determination is higher than the binding energy in the elemental metal, it can be determined that the element as the object of determination is positively charged and the element exists as a cation. Similarly, whether there is a lone electron pair can also be judged based on the binding energy obtained by XPS determination.
[0105] The antiperovskite structure contained in the dielectric 20 is not limited to a specific structure. The antiperovskite structure may be a NH4Pb2Br5 structure, a Cs3CoCl5 structure, a La2CuSbS5 structure, or a La4FeSb2S 10 Type structure, it can be Ba4In2Te2S5 type structure, it can be Y2HfS5 type structure, it can be TlPb2Cl5 type structure.
[0106] For example, Figure 5A , Figure 5B and Figure 5C The CsSn2Cl5 shown has a NH4Pb2Br5 type structure with space group I4 / mcm. Fig. 6A is a diagram showing the crystal structure of CsSn2Cl4Br represented by a coordination polyhedron centered on an anion, Figure 6B It is viewed along the negative direction of the c-axis Fig. 6A The crystal structure shown in FIG. CsSn2Cl4Br is also an antiperovskite structure of the NH4Pb2Br5 type with a space group of I4 / mcm. Regarding the composition of the NH4Pb2Br5 type structure, there are compositions represented by DE2O5 or DE2O4R, for example. In these compositions, D and E are cations, and Q and R are anions. In CsSn2Cl5, as described above, Cl4 is configured at the A site. 4- , with Cl at site B - , Cs is configured at the X site + or Sn 2+ Therefore, CsSn2Cl5 is represented as (Cl4)Cl(CsSn2) in ABX3 notation. Cs is arranged at the vertices of the octahedron sharing the vertices. + or Sn 2+ At the center of the octahedron is Cl - .
[0107] Regarding the composition of the NH4Pb2Br5 type structure, in addition to the above-mentioned composition, there may also be a composition represented by DEGQ5 or DEGQ4R. In these compositions, D, E and G are cations, and Q and R are anions. For example, Fig. 7A As shown, by replacing the Sn site of CsSn2Cl5 with Sn 2+ and Pb 2+ These two cation substitutions can yield the composition of CsSnPbCl5. Figure 7B It is viewed along the negative direction of the c-axis Fig. 7A The crystal structure shown in FIG. 1 is shown in FIG. 1 . Furthermore, depending on the occupancy, the symmetry may sometimes be reduced from the space group I4 / mcm.
[0108] Regarding the composition of NH4Pb2Br5 type structure, in addition to the above composition, DEG4Q can also be used. 10 or DEG4Q8R2. In these compositions, D, E and G are cations, and Q and R are anions. For example, Fig. 8A As shown, by replacing the Cs site of CsSn2Cl5 with K + and Cs + These two cation substitutions can obtain KCsSn4Cl 10 composition. Figure 8B It is viewed along the negative direction of the c-axis Fig. 8A The crystal structure shown in FIG. 1 is shown in FIG. 1 . Furthermore, depending on the occupancy, the symmetry may sometimes be reduced from the space group I4 / mcm.
[0109] Fig. 9A is a diagram showing the crystal structure of Cs3CoCl5 represented by a coordination polyhedron centered on an anion, Fig. 9B It is viewed along the negative direction of the c-axis Fig. 9A Figure 2 shows the crystal structure of the Fig. 10A is a diagram showing the crystal structure of Ba3AlO4F represented by coordination polyhedra centered on anions, Fig. 10B It is viewed along the negative direction of the c-axis Fig. 10A Figure 2 shows the crystal structure of the Fig.11A is a diagram showing the crystal structure of BaLa2ZnO5 represented by a coordination polyhedron centered on an anion, Fig. 11B It is viewed along the negative direction of the c-axis Fig.11A Figure 2 shows the crystal structure of the Fig. 12A is a diagram showing the crystal structure of CsBa2SnS4Cl represented by a coordination polyhedron centered on an anion, Fig. 12B It is viewed along the negative direction of the c-axis Fig. 12A The crystal structure shown in Figure 1 is an antiperovskite structure of space group I4 / mcm. In this structure, Cl is arranged at each vertex of the tetrahedron.- and the anions, and Co is arranged at the center of the tetrahedron. 2+ The cations are cations, and the anions are polyatomic ions occupying the A sites. The compositions of the Cs3CoCl5 type structure are represented, for example, as D3EQ5, D3EQ4R, DE2GQ5, and DE2GQ4R. In these compositions, D, E, and G are cations, and Q and R are anions. Fig. 9A and Fig. 9B As shown, for example, in Cs3CoCl5, (CoCl4) is configured at the A site 2- , with Cl at site B - , Cs is configured at the X site + Therefore, Cs3CoCl5 is represented as (CoCl4)ClCs3 in ABX3 notation. Cs is arranged at the vertices of the octahedron sharing the vertices. + At the center of the octahedron is Cl - .
[0110] Fig.13A is a diagram showing the crystal structure of La2CuSbS5 represented by a coordination polyhedron centered on an anion. Fig. 13B It is viewed along the negative direction of the c-axis Fig.13A The crystal structure shown in FIG. This crystal structure is an antiperovskite structure of space group Ima2. In this structure, S2 is arranged at each vertex of the tetrahedron. - and other anions, and a Cu + The cations are polyatomic ions, and the anions are polyatomic ions occupying the A sites. The compositions of the La2CuSbS5 type structure are represented, for example, as D3EQ5, D3EQ4R, DE2GQ5, and DE2GQ4R. In these compositions, D, E, and G are cations, and Q and R are anions. Fig.13A and Fig. 13B As shown, for example, in La2CuSbS5, (CuS4) is configured at the A site 7- , S is configured at the B site 2- , La is configured at the X site 3+ and Sb 3+ Therefore, La2CuSbS5 is expressed as (CuS4)S(La2Sb) in ABX3 notation. La is arranged at the vertices of the octahedron sharing the vertices. 3+ and Sb 3+ , S is arranged at the center of the octahedron 2- The La2CuSbS5 structure is basically the same as the Cs3CoCl5 structure, but due to the replacement of the Cs site with La 3+ and Sb 3+, the Cl-Co octahedron of the Cs3CoCl5 type structure is distorted, resulting in a decrease in symmetry, becoming a La2CuSbS5 type structure.
[0111] Fig.14A is a diagram showing La4FeSb2S represented by a coordination polyhedron centered on an anion 10 The crystal structure of Fig. 14B It is viewed along the negative direction of the c-axis Fig.14A The crystal structure shown in FIG. This crystal structure is an antiperovskite structure of the space group Pbcm. In this structure, S is arranged at each vertex of the tetrahedron. 2- and the like anions, and Fe is partially arranged in the center of the tetrahedron. 2+ Isocations, anions of polyatomic ions occupy the A site. La4FeSb2S 10 The composition of the type structure is as follows: 10 , D6EQ8R2, D2E4GQ5 and D2E4GQ8R2. In these compositions, D, E and G are cations, and Q and R are anions. Fig.14A and 14B As shown, for example, in La4FeSb2S 10 In the A site, (FeS4) is configured 6- , S is configured at the B site 2- , La is configured at the X site 3+ and Sb 3+ Therefore, La4FeSb2S 10 When A2B2X6 is used as the notation, it is expressed as [(FeS4)(S4)]S2(La2Sb)2. La is arranged at the vertices of the octahedron that shares the vertices. 3+ and Sb 3+ , S is arranged at the center of the octahedron 2- La4FeSb2S 10 The structure of the Cs3CoCl5 type is basically the same as that of the Cs3CoCl5 type, but due to the partial loss of the Co site in the center of the Co-Cl tetrahedron in the Cs3CoCl5 type structure, the symmetry is reduced, becoming La4FeSb2S 10 Type structure.
[0112] Fig.15A is a diagram showing the crystal structure of Ba4In2Te2S5 represented by a coordination polyhedron centered on an anion, Fig. 15B It is viewed along the negative direction of the c-axis Fig.15AThe crystal structure shown in the figure. Ba4In2Te2S5 has a layered antiperovskite structure. The composition of the Ba4In2Te2S5 structure is represented as D2E4Q7, D2E4Q5R2, DE3G2Q7 and DE3G2Q5R2. In these compositions, D, E and G are cations, and Q and R are anions. Fig.15A and Fig. 15B As shown, Ba4In2Te2S5 is configured with (InS2Te)2 at the A site in the layered perovskite structure A2BX4. 6- , S is configured at the B site 2- , Ba is configured at the X site 2+ Therefore, Ba4In2Te2S5 is expressed as (InS2Te)2SBa4 when A2BX4 is used. Ba is arranged at the vertices of the octahedron sharing the vertices. 2+ , S is arranged at the center of the octahedron 2- .
[0113] Fig.16A is a diagram showing the crystal structure of Y2HfS5 represented by a coordination polyhedron centered on an anion, Fig. 16B It is viewed along the negative direction of the c-axis Fig.16A The crystal structure shown in FIG. Y2HfS5 is an antiperovskite structure of space group Pnma. Regarding the composition of the Y2HfS5 type structure, there are compositions represented by DE2Q5 or DE2Q4R, for example. In these compositions, D and E are cations, and Q and R are anions. In Y2HfS5, as described above, S4 is configured at the A site. 8- , S is configured at the B site 2- , with Y configured at the X site 3+ or Hf 4+ Therefore, Y2HfS5 is expressed as (S4)S(Y2Hf) when expressed as ABX3. Y is arranged at the vertices of the octahedron that shares the vertices. 3+ or Hf 4+ , S is arranged at the center of the octahedron 2- . The NH4Pb2Br5 type structure is based on a tetragonal perovskite structure (SrZrO3). On the other hand, the Y2HfS5 type structure is based on an orthorhombic perovskite structure (GdFeO3). The tetragonal perovskite type structure has a structure in which octahedrons are linearly connected in the c-axis direction, but the orthorhombic perovskite type structure has a structure in which octahedrons are connected in a zigzag manner in the c-axis direction. Furthermore, from the perspective of being a dielectric, since the relative dielectric constant of the tetragonal perovskite type structure linearly connected in the c-axis direction becomes higher, the NH4Pb2Br5 type structure is more advantageous than the Y2HfS5 type structure.
[0114] Fig.17A is a diagram showing the crystal structure of TlPb2Cl5 represented by a coordination polyhedron centered on an anion, Fig. 17B It is viewed along the negative direction of the c-axis Fig.17A The crystal structure shown in FIG. TlPb2Cl5 is an antiperovskite structure of space group P121 / C1. Regarding the composition of the TlPb2Cl5 type structure, there are compositions represented by DE2Q5 or DE2Q4R. In these compositions, D and E are cations, and Q and R are anions. In TlPb2Cl5, as described above, Cl4 is configured at the A site. 4- , with Cl at site B - , Tl is configured at the X site + or Pb 2+ Therefore, TlPb2Cl5 is represented as (Cl4)Cl(TlPb2) in ABX3 notation. Tl is arranged at the vertices of the octahedron sharing the vertices. + or Pb 2+ At the center of the octahedron is Cl - . The TlPb2Cl5 structure is based on the orthorhombic perovskite structure (GdFeO3) like the Y2HfS5 structure. In the Y2HfS5 structure, the cations of Y and Hf are arranged alternately along the c-axis in an octahedron, but this is not the case with the TlPb2Cl5 structure. Furthermore, from the perspective of being a dielectric, the relative dielectric constant of the tetragonal perovskite structure connected linearly in the c-axis direction becomes higher, so the NH4Pb2Br5 structure is more advantageous than the Y2HfS5 structure.
[0115] As perovskite structures in which anions are arranged at the vertices of an octahedrons sharing vertices and cations are arranged at the center of the octahedron, there are one-dimensional perovskite structure, zero-dimensional perovskite structure, double perovskite structure, quadruple perovskite structure, A-site defect perovskite structure, B-site defect perovskite structure, Ruddlesden-Popper structure, and Dion-Jacobson structure. The one-dimensional perovskite structure is represented by A3BX5, and the zero-dimensional perovskite structure is represented by A4BX6. The double perovskite structure is represented by A2BB'X6, and the quadruple perovskite structure is represented by AA'3B4X 12 A-site defect perovskite structure is represented by A (2-α) B2X6 represents the B-site defect perovskite structure, and A2B represents the B-site defect perovskite structure. (2-β) X6 indicates. Ruddlesden-Popper type structure is represented by A x+1 B x X 3x+1 A'[Ay-1 B y X 3y+1 In any structure, there can be an antiperovskite structure in which the site of an anion and the site of a cation are exchanged. The antiperovskite structure contained in the dielectric 20 may also be such an antiperovskite structure.
[0116] The relative dielectric constant of the dielectric 20 is not limited to a specific value. The relative dielectric constant of the dielectric 20 at room temperature may be, for example, higher than 40, may be 45 or more, may be 50 or more, may be 60 or more, may be 80 or more, or may be 100 or more at 1 MHz. The room temperature is, for example, a specific temperature in the range of 20° C. to 25° C. The relative dielectric constant of the dielectric 20 at room temperature may be, for example, 10,000 or less at 1 MHz. In other words, the relative dielectric constant of the dielectric 20 at room temperature may be, for example, 40 or more and 10,000 or less at 1 MHz.
[0117] like Figure 3 As shown, in the capacitor 1a, the dielectric 20 is formed, for example, as a film. The method of configuring the dielectric 20 in the capacitor 1a is not limited to a specific method. The dielectric 20 can be formed by, for example, spin coating, inkjet, die coating, roller coating, rod coating, Langmuir-Blodgett method, dip coating or spraying. As a result, the dielectric 20 is more likely to have a high relative dielectric constant, and the capacitor 1a is more likely to have a high electrostatic capacitance. The dielectric 20 can also be formed by sputtering, anodization, vacuum evaporation, pulsed laser deposition (PLD), atomic layer deposition (ALD) or chemical vapor growth (CVD).
[0118] like Figure 3 As shown, the dielectric 20 is disposed between the first electrode 11 and the second electrode 12, for example, in the thickness direction of the dielectric 20. The second electrode 12 covers at least a portion of the dielectric 20, for example.
[0119] The materials constituting the first electrode 11 and the second electrode 12 are not limited to specific materials. The first electrode 11 and the second electrode 12 each contain, for example, a metal. The first electrode 11 contains, for example, a valve metal. Examples of valve metals are Al, Ta, Nb, and Bi. The first electrode 11 contains, for example, at least one selected from Ta, Nb, and Bi as a valve metal. The first electrode 11 may contain a noble metal such as gold and platinum, may contain nickel, and may contain a metal element in Group 13, Group 14, or Group 15.
[0120] The second electrode 12 may include, for example, valve metals such as Al, Ta, Nb, and Bi, may include precious metals such as gold, silver, and platinum, may include nickel, and may include a metal element in Group 13, Group 14, or Group 15. The second electrode 12 may include, for example, at least one selected from the group consisting of Al, Ta, Nb, Bi, gold, silver, platinum, and nickel.
[0121] like Figure 3 As shown, the first electrode 11 has a main surface 11p. One main surface of the dielectric 20 is in contact with the main surface 11p, for example. The second electrode 12 has a main surface 12p parallel to the main surface 11p. The other main surface of the dielectric 20 is in contact with the main surface 12p, for example.
[0122] Fig.18A This is a cross-sectional view showing another example of the capacitor of the present disclosure. Fig.18A The capacitor 1b shown is constructed in the same manner as the capacitor 1a except for the parts specifically described. The components of the capacitor 1b that are the same as or correspond to the components of the capacitor 1a are given the same reference numerals, and detailed descriptions are omitted. The descriptions of the capacitor 1a are also applicable to the capacitor 1b as long as they are not technically contradictory. Furthermore, these situations also apply to the capacitors 1c and 1d described later.
[0123] Fig.18A The capacitor 1b shown is an electrolytic capacitor. Fig.18A As shown, in the capacitor 1b, at least a portion of the first electrode 11 is porous. According to such a structure, the surface area of the first electrode 11 is likely to be increased, and the capacitor 1b is likely to have a higher electrostatic capacitance. Such a porous structure can be formed by, for example, etching of metal foil and sintering of powder.
[0124] like Fig.18A As shown, for example, a film of a dielectric 20 is formed on the surface of the porous portion of the first electrode 11. As a method for forming the dielectric 20, for example, spin coating, inkjet, die coating, roller coating, rod coating, Langmuir-Blodgett method, dip coating or spray coating can be used. The dielectric 20 can also be formed by, for example, sputtering, anodization, vacuum evaporation, PLD, ALD or CVD.
[0125] The first electrode 11 includes, for example, a valve metal such as Al, Ta, Nb, Zr, Hf, and Bi. The second electrode 12 may also include, for example, a solidified material of a silver-containing paste, a carbon material such as graphite, or both of the solidified material and the carbon material. In the capacitor 1b, for example, an electrolyte 13 is arranged between the first electrode 11 and the second electrode 12. Specifically, an electrolyte 13 is arranged between the dielectric 20 and the second electrode 12. In the capacitor 1b, for example, the second electrode 12 and the electrolyte 13 constitute a cathode. In the capacitor 1b, the electrolyte 13 is arranged, for example, to fill the gaps around the porous part of the first electrode 11.
[0126] The electrolyte 13 includes, for example, at least one selected from an electrolyte solution and a conductive polymer. Examples of the conductive polymer are polypyrrole, polythiophene, polyaniline, and derivatives thereof. The electrolyte 13 may also be a manganese compound such as manganese oxide. The electrolyte 13 may also include a solid electrolyte.
[0127] Electrolyte 13 containing a conductive polymer substance can be formed by chemically polymerizing, electrolytically polymerizing, or both chemically polymerizing and electrolytically polymerizing raw material monomers on dielectric 20. Electrolyte 13 containing a conductive polymer substance can also be formed by attaching a solution or dispersion of a conductive polymer substance to dielectric 20.
[0128] Fig.18B is a cross-sectional view showing another example of the capacitor disclosed in the present invention. Fig.18B In the capacitor 1c shown, at least a portion of the first electrode 11 is porous. With such a structure, the surface area of the first electrode 11 is easily increased, and the capacitor 1c is easily provided with a higher electrostatic capacitance. Such a porous structure can be formed, for example, by etching of metal foil and sintering of powder.
[0129] like Fig.18B As shown, for example, a film of a dielectric 20 is formed on the upper part of the porous part of the first electrode 11. As a film forming method of the dielectric 20, for example, spin coating, ink jet, die coating, roller coating, rod coating, Langmuir-Blodgett method, dip coating or spray coating can be used. In the capacitor 1c, the dielectric 20 is arranged in a manner to fill the gap around the porous part of the first electrode 11, for example.
[0130] Fig. 18C is a cross-sectional view showing another example of the capacitor disclosed in the present invention. Fig. 18CIn the capacitor 1d shown, the dielectric 20 is formed, for example, as a film. In the film, a heterogeneous dielectric 22 different from the dielectric 20 is dispersed. As a method for forming the film, spin coating, inkjet, die coating, roller coating, rod coating, Langmuir-Blodgett method, dip coating or spray coating can be used. For example, by forming a coating film of a precursor liquid containing a raw material of the dielectric 20 and particles of the heterogeneous dielectric 22 by the above method, a film containing the dielectric 20 and the heterogeneous dielectric 22 can be obtained. The film can also be formed by sputtering, anodization, vacuum evaporation, PLD, ALD or CVD.
[0131] The heterogeneous dielectric 22 is not limited to a specific dielectric as long as it is a dielectric of a different type from the dielectric 20. The heterogeneous dielectric 22, for example, has a relative dielectric constant higher than the relative dielectric constant of the dielectric 20. The heterogeneous dielectric 22 may be, for example, a perovskite compound such as BaTiO3, PbTiO3, and SrTiO3, or a layered perovskite compound. The heterogeneous dielectric 22 may also include at least one selected from a Ruddlesden-Popper compound, a Dion-Jacobson compound, a tungsten bronze compound, and a pyrochlore compound.
[0132] The size of the particles of the different dielectric material 22 is not limited to a specific value. The particles of the different dielectric material 22 have a size of, for example, 1 nm or more and 100 nm or less.
[0133] Fig.19A Schematically showing an example of a circuit of the present disclosure. Circuit 3 includes capacitor 1a. Circuit 3 may be an active circuit or a passive circuit. Circuit 3 may be a discharge circuit, a smoothing circuit, a decoupling circuit, or a coupling circuit. Since circuit 3 includes capacitor 1a, circuit 3 can easily exhibit the desired performance. For example, in circuit 3, noise can be easily reduced by capacitor 1a. Circuit 3 may also include capacitor 1b, 1c, or 1d instead of capacitor 1a.
[0134] Fig.19B Schematically shows an example of a circuit board of the present disclosure. Fig.19B As shown, the circuit board 5 has a capacitor 1a. For example, the circuit 3 including the capacitor 1a is formed in the circuit board 5. The circuit board 5 may be an embedded board or a motherboard. The circuit board 5 may also have a capacitor 1b, 1c or 1d instead of the capacitor 1a.
[0135] Fig.19C Schematically shows an example of the device disclosed in the present invention. Fig.19CAs shown, the device 7 includes, for example, a capacitor 1a. The device 7 includes, for example, a circuit board 5 including the capacitor 1a. Since the device 7 includes the capacitor 1a, the device 7 can easily exert the desired performance. The device 7 can be an electronic device, a communication device, a signal processing device, or a power supply device. The device 7 can be a server, an AC adapter, an accelerator, or a flat-panel display device such as a liquid crystal display device (LCD). The device 7 can be a USB charger, a solid-state drive (SSD), an information terminal such as a PC, a smartphone, and a tablet PC, or an Ethernet switch.
[0136] Example
[0137] Hereinafter, the present disclosure will be described in more detail by way of examples. Note that the following examples are for illustration only, and the present disclosure is not limited to the following examples.
[0138] <Example 1>
[0139] (Manufacturing of dielectric materials)
[0140] In an argon atmosphere with a dew point below -60°C (hereinafter referred to as "dry argon atmosphere"), raw material powders containing KCl and SnCl2 are prepared in a manner that satisfies the condition that the amount of KCl: the amount of SnCl2 = 1:2. The raw material powders are crushed and mixed in a mortar. In this way, a mixed powder is obtained. The mixed powder is ground using a planetary ball mill at 500 rpm (revolutions per minute) for 12 hours. In this way, a powdered dielectric of Example 1 is obtained. The dielectric of Example 1 contains a halide having a composition represented by KSn2Cl5.
[0141] The dielectric of Example 1 was subjected to XPS measurement using an X-ray photoelectron spectroscopy (XPS) device PHI VersaProbe2 manufactured by ULVAC PHI. Based on the results of the measurement, the contents of K, Sn, and Cl per unit weight of the dielectric were determined. Based on the contents of K, Sn, and Cl, it was found that in the dielectric of Example 1, the amount of substance of K: the amount of substance of Sn: the amount of substance of Cl = 1:2:5 existed in the same relationship as in the raw material powder.
[0142] (Evaluation of relative dielectric constant)
[0143] Fig. 20 FIG. 2 is a diagram schematically showing a method for evaluating relative dielectric constant. Fig. 20As shown, the press forming die 30 includes a punch upper portion 31, a frame die 32, and a punch lower portion 33. The punch upper portion 31 and the punch lower portion 33 are each formed of stainless steel having electronic conductivity. The frame die 32 is formed of polycarbonate having electrical insulation.
[0144] The relative dielectric constant of the dielectric of Example 1 was measured by the following method using the press molding die 30 .
[0145] In a dry atmosphere with a dew point of -30°C or less, the powdered dielectric of Example 1 was filled into the press die 30 to obtain a sample Sa. Inside the press die 30 , a pressure P of 300 MPa was applied to the sample Sa using the punch upper portion 31 and the punch lower portion 33 .
[0146] While applying pressure P to the sample Sa, the upper punch portion 31 and the lower punch portion 33 are connected to a potentiostat 50 equipped with a frequency response analyzer. As the potentiostat 50, VersaSTAT4 manufactured by Princeton Applied Research is used. The upper punch portion 31 is connected to the working electrode and the potential measurement terminal of the potentiostat 50. The lower punch portion 33 is connected to the counter electrode and the reference electrode of the potentiostat 50. The impedance of the sample Sa was measured by electrochemical impedance measurement at room temperature (25°C). In this way, the relative dielectric constant ε of the halide contained in the dielectric of Example 1 at 1 MHz was measured. ’ r The electrostatic capacitance of each sample was measured, and the relative dielectric constant ε was determined based on the measured value of the electrostatic capacitance and the thickness and electrode area of the sample Sa. ’ r The relative dielectric constant ε is calculated using the following formula using the filling rate f of the pellet (the sample Sa compressed under pressure P): ’ r After correction, the relative dielectric constant ε is obtained r In the following formula, ε Air is the relative dielectric constant of the atmosphere. In this calculation, ε Air Set to 1.
[0147] logε r =(logε ’ r -(1-f)*logε Air ) / f
[0148] The filling rate f is calculated by the following formula. pelletis the density of the tablet, and ρ is the density obtained from the crystal structure. The results are shown in Table 1. As shown in Table 1, the relative dielectric constant ε of the halide contained in the dielectric of Example 1 measured at 25°C is r It is 119.
[0149] f=ρ pellet / ρ
[0150] (Evaluation of synthesis possibility by calculation)
[0151] A computational model for a compound of an antiperovskite structure of the (NH4)Pb2Br5 type having a composition represented by KSn2Cl5 was generated, and the convex hull energy was calculated by first-principles calculations to evaluate the synthetic feasibility of the compound. Structural relaxation was performed by first-principles calculations, and the total energy and convex hull energy were calculated. The convex hull energy is an indicator of the relative stability of the target phase relative to other phases. In the case of the dielectric of Example 1 having a composition of KSn2Cl5, since it can coexist with KCl and SnCl2 thermodynamically, the convex hull energy was calculated based on the following formula (1). The results are shown in Table 1. In formula (1), E hull (A) is the convex hull energy of A, and Etot(A) is the total energy of A. Furthermore, in E hull When (A) is a negative value, the value of equation (1) is regarded as zero.
[0152] E hull (KSn2Cl5)=Etot(KSn2Cl5)-Etot(KCl)-2Etot(SnCl2) Formula (1)
[0153] (Evaluation of relative dielectric constant by calculation)
[0154] Using the calculation model generated in the evaluation of the above-mentioned synthesis possibility, the structure relaxation was performed again using the PBEsol functional, and the relative dielectric constant was evaluated by density functional perturbation theory calculation. The contribution of ions and electrons was added together, and the diagonal elements were averaged to calculate the relative dielectric constant. Furthermore, from the perspective of calculation accuracy, compounds with virtual phonons greater than 5meV at the G point and compounds with zero band gap were removed. The results are shown in Table 1. The vasp code was used in the first-principles calculation.
[0155] (Polarized Evaluation)
[0156] Based on the relative dielectric constant ε determined in the evaluation of the relative dielectric constant using the above-mentioned sample Sa r, the calculated value of the polarization P of the dielectric of Example 1 is calculated by the following formula (2). The results are shown in Table 1. In formula (2), ε0 is the dielectric constant of vacuum, and E is the insulation breakdown electric field. The insulation breakdown electric field E refers to Wang Li-Mo. "Relationship between intrinsic breakdown field and bandgap of materials." 2006 25th International Conference on Microelectronics. IEEE, 2006. (Wang, Li-Mo. "Relationship between intrinsic breakdown field and bandgap of materials." 2006 25th International Conference on Microelectronics. IEEE, 2006.), and is calculated by the following formula (3). In formula (3), E g is the band gap and is assumed to be 4 eV in this calculation. E and E in equations (2) and (3) are g The units are V / cm and eV respectively.
[0157] P = ε0(ε r -1)E Formula (2)
[0158] E = 1.36 × 10 7 ×(E g / 4) Formula (3)
[0159] (Crystal structure analysis)
[0160] X-ray diffraction (XRD) measurement was performed to identify the crystal structure of the dielectric of Example 1. In this measurement, Cu-Kα rays were used as X-rays, and the measurement was performed in a dry argon atmosphere. Fig.21 Graph showing the XRD spectrum of the dielectric of Example 1. The horizontal axis represents the diffraction angle 2θ, and the vertical axis represents the intensity of X-ray diffraction. Fig.21 The calculation results of XRD patterns of KCl, SnCl2 and (NH4)Pb2Br5 type KSn2Cl5 are shown in FIG. Fig.21 The vertical axis in shows the relative relationship of the diffraction intensity in each XRD spectrum, and does not show the relative relationship of the diffraction intensity in different XRD patterns. According to the XRD spectrum of the dielectric of Example 1, it is confirmed that the dielectric has an antiperovskite structure of (NH4)Pb2Br5 type.
[0161] <Example 2>
[0162] The powdered dielectric of Example 2 was prepared in the same manner as in Example 1 except that the raw material powder containing KBr and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of KBr: the amount of substance of SnCl2 = 1:2. The composition of the dielectric of Example 2 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 2, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0163] <Example 3>
[0164] The powdered dielectric of Example 3 was prepared in the same manner as in Example 1 except that the raw material powder containing KBr and SnBr2 was prepared in such a manner that the amount of substance of KBr: the amount of substance of SnBr2 = 1:2. The composition of the dielectric of Example 3 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 3, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0165] <Example 4>
[0166] The powdered dielectric of Example 4 was prepared in the same manner as in Example 1 except that the raw material powder containing K(SCN) and SnCl2 was prepared in such a manner that the amount of substance of K(SCN):the amount of substance of SnCl2=1:2. - It is a cluster anion with a valence of -1 and is treated as SCN - The composition of the dielectric of Example 4 was determined based on XPS measurement in the same manner as in Example 1. In addition, the dielectric of Example 4 was evaluated for relative dielectric constant in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0167] <Example 5>
[0168] The powdered dielectric of Example 5 was prepared in the same manner as in Example 1 except that the raw material powder containing KCl and SnBr2 was prepared in a manner that satisfied the condition of the amount of substance of KCl: the amount of substance of SnBr2 = 1:2. The composition of the dielectric of Example 5 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 5, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0169] <Example 6>
[0170] The powdered dielectric of Example 6 was prepared in the same manner as in Example 1 except that the raw material powder containing KI and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of KI: the amount of substance of SnCl2 = 1:2. The composition of the dielectric of Example 6 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 6, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0171] <Example 7>
[0172] The powdered dielectric of Example 7 was prepared in the same manner as in Example 1 except that the raw material powder containing KF, KCl and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of KF: the amount of substance of KCl: the amount of substance of SnCl2 = 0.5:0.5:2. The composition of the dielectric of Example 7 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 7, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0173] <Example 8>
[0174] The powdered dielectric of Example 8 was prepared in the same manner as in Example 1 except that the raw material powder containing KI and SnI2 was prepared in such a manner that the amount of substance of KI: the amount of substance of SnI2 = 1:2. The composition of the dielectric of Example 8 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 8, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0175] <Example 9>
[0176] The powdered dielectric of Example 9 was prepared in the same manner as in Example 1 except that the raw material powder containing KCl, SnCl2 and PbCl2 was prepared in a manner that satisfied the condition of the amount of substance of KCl: the amount of substance of SnCl2: the amount of substance of PbCl2 = 1:1:1. The composition of the dielectric of Example 9 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 9, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0177] <Example 10>
[0178] The raw material powder containing RbCl and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of RbCl: the amount of substance of SnCl2 = 1:2, and the powdered dielectric of Example 10 was prepared in the same manner as in Example 1. The composition of the dielectric of Example 10 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 10, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. Moreover, the relative dielectric constant and convex hull energy of the dielectric of Example 10 were calculated in the same manner as in Example 1. The results are shown in Table 1.
[0179] <Example 11>
[0180] The powdered dielectric of Example 11 was prepared in the same manner as in Example 1 except that the raw material powder containing CsBr and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of CsBr: the amount of substance of SnCl2 = 1:2. The composition of the dielectric of Example 11 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 11, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0181] <Example 12>
[0182] The raw material powder containing CsCl and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of CsCl: the amount of substance of SnCl2 = 1:2, and the powdered dielectric of Example 12 was prepared in the same manner as in Example 1. The composition of the dielectric of Example 12 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 12, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. Moreover, the relative dielectric constant and convex hull energy of the dielectric of Example 12 were calculated in the same manner as in Example 1. The results are shown in Table 1.
[0183] <Example 13>
[0184] The powdered dielectric of Example 13 was prepared in the same manner as in Example 1 except that the raw material powder containing InI and SnCl2 was prepared in a manner that satisfied the condition of the amount of substance of InI: the amount of substance of SnCl2 = 1:2. The composition of the dielectric of Example 13 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 13, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. The results are shown in Table 1.
[0185] <Example 14>
[0186] A raw material powder containing InI and SnI2 was prepared in a manner that satisfies the condition that the amount of substance of InI: the amount of substance of SnI2 = 1:2, and a powdered dielectric of Example 14 was produced in the same manner as in Example 1. The composition of the dielectric of Example 14 was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Example 14, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. Moreover, the relative dielectric constant and convex hull energy of the dielectric of Example 14 were calculated in the same manner as in Example 1. The results are shown in Table 1.
[0187] <Comparative Example 1A>
[0188] The raw material powder containing CsCl and PbCl2 was prepared in a manner that satisfied the condition of the amount of substance of CsCl: the amount of substance of PbCl2 = 1:1, and the powdered dielectric of Comparative Example 1A was prepared in the same manner as in Example 1. The composition of the dielectric of Comparative Example 1A was determined based on XPS measurement in the same manner as in Example 1. In addition, for the dielectric of Comparative Example 1A, the relative dielectric constant was evaluated in the same manner as in Example 1, and the crystal structure was identified based on XRD measurement. Moreover, the relative dielectric constant and convex hull energy of the dielectric of Comparative Example 1A were calculated in the same manner as in Example 1. The results are shown in Table 8.
[0189] <Comparative Example 2>
[0190] The powdered dielectric of Comparative Example 2 was prepared in the same manner as in Example 1 except that the raw material powder containing (CH3NH3)Cl and SnCl2 was prepared in such a manner that the amount of substance of (CH3NH3)Cl: the amount of substance of SnCl2 = 1:1. The composition of the dielectric of Comparative Example 2 was determined based on XPS measurement in the same manner as in Example 1. In addition, the relative dielectric constant of the dielectric of Comparative Example 2 was evaluated in the same manner as in Example 1. The results are shown in Table 8. Fig. 22 : is a graph showing the XRD spectrum of the dielectric of Comparative Example 2. The horizontal axis represents the diffraction angle 2θ, and the vertical axis represents the intensity of X-ray diffraction. Fig. 22 The calculation results of XRD patterns of perovskite CH3NH3SnCl3, CH3NH3Cl and SnCl2 are also shown. Fig. 22 The vertical axis in represents the relative relationship of diffraction intensities of each XRD pattern, and does not represent the relative relationship of diffraction intensities between different XRD patterns. From the XRD pattern of the dielectric of Comparative Example 2, it was confirmed that the dielectric had a perovskite-type crystal structure.
[0191] <Comparative Example 3>
[0192] The ferroelectric material of the antiperovskite structure represented by [(CH3)2(F-CH2CH2)NH]3(CdCl3)(CdCl4) described in Non-Patent Document 1 was selected as the dielectric of Comparative Example 3. Figure 3 (c) The relative dielectric constant of the dielectric of Comparative Example 3 at room temperature and 1 MHz was read. As a result, the relative dielectric constant of the dielectric of Comparative Example 3 at room temperature and 1 MHz was 15.4. It can be understood that the dielectric of Comparative Example 3 can be produced with reference to the experimental section of Non-Patent Document 1.
[0193] <Example 15>
[0194] A computational model of an antiperovskite structure of (NH4)Pb2Br5 type having a composition of CsSn2Br5 was generated. In the generation of the computational model, (NH4)Pb2Br5 was elementally substituted in such a way as to achieve a symmetry of I4 / mcm, and the most stable structure was determined based on first-principles calculations. For the obtained computational model, the convex hull energy and relative dielectric constant were calculated by first-principles calculations, similarly to the evaluation of the possibility of synthesis by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 1.
[0195] <Example 16 to Example 50>
[0196] Except for changing the composition of the calculation model as shown in Table 1, Table 2 or Table 3, the calculation models of Examples 16 to 50 were generated in the same manner as in Example 15. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 1, Table 2 or Table 3.
[0197] <Example 51>
[0198] A computational model of an antiperovskite structure of (NH4)Pb2Br5 type with a composition of CsSnPbCl5 was generated. In the generation of the computational model, (NH4)Pb2Br5 was elementally substituted in a manner to achieve the symmetry of P4_2 / mcm, and the most stable structure was determined based on first-principles calculations. For the obtained computational model, the convex hull energy and relative dielectric constant were calculated by first-principles calculations, similarly to the evaluation of the possibility of synthesis by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 3.
[0199] <Example 51 to Example 60>
[0200] Except for changing the composition of the calculation model as shown in Table 3, the calculation models of Examples 51 to 60 were generated in the same manner as in Example 51. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 3.
[0201] <Example 61>
[0202] A computational model of an antiperovskite structure of (NH4)Pb2Br5 type having a composition of CsIn(Pb2Cl5)2 was generated. In the generation of the computational model, (NH4)Pb2Br5 was elementally substituted in such a way as to achieve the symmetry of P4 / mcc, and the most stable structure was determined based on first-principles calculations. For the obtained computational model, the convex hull energy and relative dielectric constant were calculated by first-principles calculations, similarly to the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 4.
[0203] <Example 62 to Example 105>
[0204] Except for changing the composition of the calculation model as shown in Table 4, Table 5 or Table 6, the calculation models of Examples 62 to 105 were generated in the same manner as in Example 61. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first principle calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 4, Table 5 or Table 6.
[0205] <Example 106>
[0206] A computational model of an antiperovskite structure of the Cs3CoCl5 type having a composition of ZnIn3Cl5 was generated. In the generation of the computational model, Cs3CoCl5 was elementally substituted in such a way as to achieve a symmetry of I4 / mcm, and the most stable structure was determined based on first-principles calculations. For the obtained computational model, the convex hull energy and relative dielectric constant were calculated by first-principles calculations, similarly to the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 6.
[0207] <Example 107 to Example 123>
[0208] Except for changing the composition of the calculation model as shown in Table 6 or Table 7, the calculation models of Examples 107 to 123 were generated in the same manner as in Example 106. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 6 or Table 7.
[0209] <Example 124>
[0210] A computational model of an antiperovskite structure of the La2SbCuS5 type having a composition of InBa2SbS5 was generated. In the generation of the computational model, La2SbCuS5 was elementally substituted in such a way as to obtain the symmetry of Ima2, and the most stable structure was determined based on the first-principles calculation. For the obtained computational model, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 7.
[0211] <Example 125 to Example 135>
[0212] Except for changing the composition of the calculation model as shown in Table 7, the calculation models of Examples 125 to 135 were generated in the same manner as in Example 124. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 6 or Table 7.
[0213] <Example 136>
[0214] The Pb2In4ZnF 10 The composition of La4FeSb2S 10 In the generation of the computational model, La4FeSb2S was symmetric to obtain the Pbcm structure. 10 The element substitution was performed, and the most stable structure was determined based on the first principle calculation. For the obtained calculation model, the convex hull energy and the relative dielectric constant were calculated by first principle calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 7.
[0215] <Example 137 to Example 149>
[0216] Except for changing the composition of the calculation model as shown in Table 7 or Table 8, the calculation models of Examples 137 to 149 were generated in the same manner as in Example 136. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 7 or Table 8.
[0217] <Example 150>
[0218] A computational model of a Ba4In2Te2S5 type antiperovskite structure with a composition of Al2Pb4S7 was generated. In generating the computational model, La4FeSb2S was symmetric to achieve P4 / mbm. 10 The element substitution was performed, and the most stable structure was determined based on the first principle calculation. For the obtained calculation model, the convex hull energy and the relative dielectric constant were calculated by first principle calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 8.
[0219] <Example 151 and Example 152>
[0220] The calculation models of Examples 151 and 152 were generated in the same manner as in Example 150 except that the composition of the calculation model was changed as shown in Table 8. For the obtained calculation models, the convex hull energy and the relative dielectric constant were calculated by first-principles calculation in the same manner as the evaluation of the synthesis possibility by calculation and the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 8.
[0221] <Comparative Example 1B>
[0222] A CsPbCl3 composition was generated, in which Cl was arranged at the vertices of multiple octahedrons sharing a face. - , Pb is arranged at the center of the octahedron 2+ A calculation model of a perovskite structure of . Using this calculation model, the relative dielectric constant was calculated by first-principles calculation in the same manner as the evaluation of the relative dielectric constant by calculation in Example 1. The results are shown in Table 1.
[0223] according to Fig.21 and Fig. 22, it is confirmed that the dielectric of Comparative Example 2 has a perovskite structure, while the dielectric of Example 1 has an antiperovskite structure of the (NH4)Pb2Br5 type. The XRD spectra of the dielectrics of Examples 2 to 14 confirm that the dielectrics of Examples 2 to 14 also have an antiperovskite structure of the (NH4)Pb2Br5 type. As shown in Tables 1 to 8, the measured values or calculated values of the relative dielectric constants of the dielectrics or calculation models of Examples 1 to 152 exceed 40. The dielectrics of these embodiments have an antiperovskite structure in which cations are arranged at the vertices of multiple octahedrons sharing vertices, and anions are arranged at the center of the octahedron. The relative dielectric constants of the perovskite dielectrics of Comparative Examples 1A and Comparative Examples 2 are less than 40.0. In addition, the relative dielectric constant of the dielectric of Comparative Example 3, which has an antiperovskite structure in which cations are arranged at the vertices of multiple octahedrons sharing a face, and anions are arranged at the center of the octahedron, is also less than 40. Therefore, the calculated values of polarization in Examples 1, 3, 5, 8, 10, 12, 14 to 152 are also higher than the calculated values of polarization in Comparative Examples 1A and 1B. By comparing Comparative Example 1A and Comparative Example 1B, it can be understood that the compound of the perovskite structure has a higher relative dielectric constant when multiple octahedrons share vertices than when multiple octahedrons share faces. Therefore, it can be understood that the antiperovskite structure having a portion in which cations are arranged at the vertices of multiple octahedrons sharing vertices and anions are arranged at the center of the octahedron is advantageous from the viewpoint of a high relative dielectric constant.
[0224] According to the following literature, it is understood that the material can be synthesized if the convex hull energy is 0.1 eV / atom or less. Therefore, as shown in Table 1, it is suggested that the compounds of the calculation model of Examples 15 to 152 can be synthesized.
[0225] S.Wenhao, et al. "The thermodynamic scale of inorganic crystalline metastability." Science advances 2.11(2016):e1600225.
[0226]
[0227]
[0228]
[0229]
[0230]
[0231]
[0232]
[0233]
[0234] Industrial Applicability
[0235] The capacitor disclosed herein easily has a high electrostatic capacitance and is useful.
Claims
1. A capacitor having: a first electrode; a second electrode; and a dielectric disposed between the first electrode and the second electrode, The dielectric contains an antiperovskite-type compound, The antiperovskite structure has a portion where cations are arranged at the vertices of a plurality of octahedrons that share a vertex, and anions are arranged at the center of the octahedron.
2. The capacitor according to claim 1, The compound contains an ion of an element in at least one group selected from Group 13, Group 14, and Group 15.
3. The capacitor according to claim 2, The ions have lone pairs of electrons.
4. The capacitor according to claim 1, The compound comprises a compound selected from In + 、Tl + ,Ge 2+ Sn 2+ , Pb 2+ , Sb 3+ and Bi 3+ At least one of .
5. The capacitor according to claim 1, The compound has a composition represented by DE2Q5, In the composition, D and E are cations, and Q is an anion.
6. The capacitor according to claim 1, The compound has a composition represented by DE2Q4R, In the composition, D and E are cations, and Q and R are anions.
7. The capacitor according to claim 1, The compound has a composition represented by DEGQ5, In the composition, D, E and G are cations, and Q is an anion.
8. The capacitor according to claim 1, The compound has a composition represented by DEGQ4R, In the composition, D, E and G are cations, and Q and R are anions.
9. The capacitor according to claim 1, The compound has DEG4Q 10 The composition of the representation, In the composition, D, E and G are cations, and Q is an anion.
10. The capacitor according to claim 1, The compound has a composition represented by DEG4Q8R2, In the composition, D, E and G are cations, and Q and R are anions.
11. The capacitor according to claim 1, The compound has a composition represented by D3EQ5, In the composition, D and E are cations, and Q is an anion.
12. The capacitor according to claim 1, The compound has a composition represented by D3EQ4R, In the composition, D and E are cations, and Q and R are anions.
13. The capacitor according to claim 1, The compound has a composition represented by DE2GQ5, In the composition, D, E and G are cations, and Q is an anion.
14. The capacitor according to claim 1, The compound has D6EQ 10 The composition of the representation, In the composition, D and E are cations, and Q is an anion.
15. The capacitor according to claim 1, The compound has a composition represented by D6EQ8R2, In the composition, D and E are cations, and Q and R are anions.
16. The capacitor according to claim 1, The compound has a composition represented by D2E4GQ5, In the composition, D, E and G are cations, and Q is an anion.
17. The capacitor according to claim 1, The compound has a composition represented by DE2GQ4R, In the composition, D, E and G are cations, and Q and R are anions.
18. The capacitor according to claim 1, The compound has a composition represented by D2E4GQ8R2, In the composition, D, E and G are cations, and Q and R are anions.
19. The capacitor according to claim 1, The compound has a composition represented by D2E4Q7, In the composition, D and E are cations, and Q is an anion.
20. A circuit comprising the capacitor according to any one of claims 1 to 19.
21. A circuit board comprising the capacitor according to any one of claims 1 to 19.
22. A device comprising the capacitor according to any one of claims 1 to 19.
Citation Information
Patent Citations
Ferroelectric memory device arranged by use of perovskite compound and method for manufacturing the same
JP2016171152A
Capacitor and method for manufacturing the same
JP2019021795A